Analysis of factors affecting electoral behavior with emphasis on the theory of political economy Vaydyvlvzhy dominant in the Election - Amir masoud Shahram niya; Jamil Milani; Javad Karami rad (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2017)
Political participation is one of the most complex problems of modern society, yet popular participation Hvz•h‌Hay era. In this study, the tenth presidential election in Iran as one of the most important aspects of political participation or better N‌Ha in the country, according to the electoral behavior of these approaches lie in the areas studied. The purpose of this study was to evaluate the impact of economic policies and the victory of Mahmoud Ahmadinejad in televised debates. The other hypothesis of the present study, the relationship between television debates and voters tend to Mr Ahmadi-Nejad points. This is the Joulgah part of the province's the presidential election. This paper presents a theoretical framework and political economy theory is the dominant ideology. Results of this study suggest that the economic policies Ahmdy‌Nzhad and television debates on the one hand and on the other hand There is a victory. Bh‌Gvnh‌Ay the data are the data also confirmed this. The results show that the impact of televised debates attracted a lot of votes to be elected president. Results of this study suggest that the economic policies Ahmdy‌Nzhad and television debates on the one hand and on the other hand There is a victory.